Journalism's ethical progression a twentieth-century journey - Mellinger, Gwyneth; Ferré, John P. (Lexington Books, 2020)
"Using case studies and historical analysis, this book traces changes in ways that journalists understood their ethical responsibilities during the pre-internet twentieth century. Each chapter in this book explores a historical development in the evolution of journalists' perceptions of their role as professionals"--